Detection of the awareness rate of abuse in pediatric patients admitted to emergency medicine department with injury - AKOĞLU, HALDUN (KARE PUBL, 2016)
Objective: It was aimed to investigate whether neglected and abused pediatric patients are properly recognized and reported by emergency physicians in the emergency department (ED). Methods: This prospective study was conducted on patients between 0 and 6 years of age presenting with trauma to ED. Patients were examined again by an emergency medicine specialist independent from the physician who did the first intervention during clinical follow-up phase after notification of patients presenting with trauma to emergency physician. Asked radiological examinations and clinical follow-up were performed. The suspected abuse evaluation form, consisting 12 items, which was formed by considering the forms used in previous studies was used to examine the awareness of physicians in cases of abuse suspicion. Results: A total of 126 patients were included in our study. 54% of cases (n = 68) were male and mean age was determined to be 31.3 +/- 18.9 months. It was found that no judicial records were written to 35.7% (n = 45) of our patients and that 11.1% (n = 5) of these patients were hospitalized. In 51.1% (n = 23) of patients without judicial records, multiple suspected abuse findings were identified. According to evaluation of first physician, it was found that 75.9% (n = 41) of discharged patients had no judicial records and was not considered as neglect and abuse. Conclusion: We conclude that detection rates of abuse can be increased by developing child abuse screening forms and ensuring the continuity of the necessary training programs. Copyright (C) 2016 The Emergency Medicine Association of Turkey. Production and hosting by Elsevier B.V. on behalf of the Owner. This is an open access article under the CC BY-NC-ND license(http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Neglect; Abuse; Pediatric